A collocation method for optimal control of linear systems with inequality constraints. Issue 6 (1998) - Razzaghi Razzaghi, M. M.; Nazarzadeh Nazarzadeh, J. J.; Nikravesh Nikravesh, K. Y. K. Y.
Abstract : A numerical method for solving linear quadratic optimal control problems with control inequality constraints is presented in this paper. The method is based upon hybrid function approximations. The properties of hybrid functions which are the combinations of block-pulse functions and Legendre polynomials are first presented. The operational matrix of integration is then utilized to reduce the optimal control problem to a set of simultaneous nonlinear equations. The inequality constraints are first converted to a system of algebraic equalities, these equalities are then collocated at Legendre–Gauss–Lobatto nodes. An illustrative example is included to demonstrate the validity and applicability of the technique.